Regional Government Strategies to Preserve the Keris Industry in Sumenep - Rahmadhani, Noviana Dwi; Fajar, Moh. Ibnu; Abdullah, Saiful (TRUNOJOYO LAW REVIEW, 2024)
This research aims to analyze the importance of establishing regulations for the Aeng Tong-tong tourist village in Sumenep Regency, which are used to strive to develop and promote keris sectarian culture in Sumenep Regency. This research method is legal research using a sociological juridical approach, with observation and interview methods. The results of this research indicate that the keris as one of the world's non-material human heritage requires a re-emphasis on the values and role in society contained in the keris so that there are no misunderstandings in the placement of the keris. The conclusion of this research is the form of local government legal protection as an effort to preserve the keris industry in Sumenep Regency as a form of maintaining keris cultural crafts and also making Sumenep the city of Keris with the highest number of keris makers in Sumenep Regency. This form of legal protection is so that there are clear legal regulations.